APOBEC3G is increasingly expressed on the human uterine cervical intraepithelial neoplasia along with disease progression. (7th June 2017) - Iizuka, Takashi; Wakae, Kousho; Nakamura, Mitsuhiro; Kitamura, Koichi; Ono, Masanori; Fujiwara, Hiroshi; Muramatsu, Masamichi
Abstract : Problem: APOBEC3G (A3G) is a cytidine deaminase that exhibits antiviral activity by introducing C‐to‐T hypermutation in viral DNA. We recently observed the distinct presence of C‐to‐T hypermutation of human papillomavirus DNA in uterine cervical intraepithelial neoplasia (CIN), suggesting the possible involvement of A3G in the mutation‐inducing process. Consequently, we investigated the association of A3G expression with CIN progression in this study. Method of study: Patients who had undergone cervical conization due to CIN1 (n=11), CIN2 (n=9), CIN3 (n=12), and micro‐invasive squamous cell carcinoma (n=2) were included. The expression profiles of A3G and p16 proteins in cervical lesions and A3G‐positive immune cells around the lesions were examined by immunohistochemistry. Results: Immunoreactive A3G protein was detected in the CIN and squamous cell carcinoma lesions. Its expression intensity and positive areas were increased and spread in accordance with the progression of CIN, respectively. The co‐expression of p16 was observed on the A3G‐positive atypical cells. The numbers of A3G‐positive immune cells in CIN3 lesions were significantly higher than those of CIN1‐2 lesions. Conclusion: These findings indicate that A3G is associated with CIN, suggesting its important roles in human papillomavirus‐induced pathophysiological processes such as CIN progression and viral elimination.